Homoeopathic Approach to Treating Postpartum Psychiatric Disorders (Homoeopathy for All, 2024)
Being a parent can be the most joyous period for the parents, especially for the women. But in some cases, it can be a nightmare due to depression. Back in the 4th century BC, Hippocrates described postpartum psychiatric disorders as lactational psychoses.1 The World Health Report 2005 states that women are 2-3 times more prone to experience anxiety and depression than men.2 50-80% of women experience some type of mood disturbance during their lying in period. These mood disturbances include anxiety, getting upset easily, feeling of being alone, fear of the unknown and/or feeling guilty, etc. Usually, such emotions fade down as the time passes but about 25% of women develop more significant symptoms like depression, anxiety, mood swings, etc. Among them, postpartum depression (PPD) itself constitutes up to 22% in India.3,4,5,6,7,8,9 It is known that the infant is affected with such psychiatric disorders of the mother. They may influence the infant feeding outcomes and, thus, affect the growth of the infant adversely.10,11 The exact cause of postpartum psychiatric disorders is not known but some evidence suggests that hormonal changes can be a causative factor.12 Apart from it, physical changes, personal and family history of depression, and the stress of caring for a new baby could be risk factors. It’s well known that conventional treatment has harmful effects both short-term and long term depending on the drug. On the other hand, homoeopathic medicines are safe and effective for postpartum psychiatric disorders. In this article, we have discussed how postpartum psychiatric disorders can well be managed with homoeopathy with repertorial analysis of symptoms and their indicated homoeopathic remedies with peculiar individualistic keynote symptoms.
Keywords: Hippocrates; homoeopathic